PENGARUH GAYA KEPEMIMPINAN, MODERNISASI SISTEM PERPAJAKAN, DAN BUDAYA ORGANISASI TERHADAP PENINGKATAN KINERJA PEGAWAI PADA KPP MADYA SURABAYA - Jonathan, Okky Varianda; Purwanto, Purwanto; Rahayu, Sri (POLITEKNIK LP3I JAKARTA, 2026)
Digital transformation and increasing demands for public accountability have positioned employee performance as a strategic factor in public sector organizations, particularly within tax administration institutions. This study aims to analyze the effects of leadership style, tax system modernization, and organizational culture on employee performance at the Surabaya Medium Tax Office, both partially and simultaneously. This research employs a quantitative approach with a causal associative design. The research population consists of all 124 employees of the Surabaya Medium Tax Office, with a census method applied as the sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that leadership style, tax system modernization, and organizational culture each have a positive and significant effect on employee performance. Furthermore, the three variables simultaneously exert a significant influence on employee performance, with the model demonstrating a high explanatory power. These findings emphasize that improving employee performance in tax administration institutions cannot be achieved through partial efforts alone, but rather requires synergy between effective leadership, a digitally enabled tax system, and an adaptive organizational culture. This study is expected to provide practical implications for human resource development policies and digital transformation strategies within the Directorate General of Taxes.